Leadership paradoxes in Angolan organizations: Emic paradoxes, etic paradoxes, and paradox work - Cunha, Miguel Pina e (2015)
The study departs from two assumptions. First, it considers that organizations and their leadership are inherently paradoxical and that, in that sense, dealing with paradox is a necessary component of the leadership process. Second, it explores whether the paradoxes of leadership may manifest differently in different contexts. We explore the emergence of paradox in the leadership of Angolan organizations. Angola is an economy transitioning from a centrally-planned to a market mode, and this makes it a rich site for understanding the specificities of paradoxical processes in an under-researched, “rest of the world”, context. The findings of our inductive study led to the emergence of four interrelated paradoxes and highlight the importance of paradoxical work as a management requirement.